Uji Antagonisme Lentinus cladopus LC4 terhadap Ganoderma boninense Penyebab Penyakit Busuk Pangkal Batang Kelapa Sawit - Erni Angraini (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2017)
The growth of oil palm can not be separated from disease attack. One of the diseases that attack is the Base Stem Rot disease caused by Ganoderma boninense. Efforts to control the pest and disease one of them by using Lentinus Cladopus LC4 biological controller so that the purpose of this study is to determine the potential of L.cladopus LC4 as biological controlling agent G. boninense. The method used is L. cladopus LC4 antagonism test against G. boninense. The results showed that L. cladopus LC4 had antagonistic potency against G. boninense pathogen, although the mechanism did not show any inhibition zone. Therefore, L.cladopus LC4 may be considered for the prevention and control of plant diseases in the field.